2017
DOI: 10.1007/s11356-017-0447-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophytes as potential biomonitors in peri-urban wetlands of the Middle Parana River (Argentina)

Abstract: The aims of this study were to measure the concentrations of nutrients and pollutants in peri-urban wetlands, to analyze the plant morphology of the most representative macrophyte species, and to determine their potential use as biomonitors. Four wetlands in the Middle Paraná River floodplain evidencing contamination or anthropogenic impact were studied. The studied species were Typha domingensis Pers., Eichhornia crassipes (Mart.) Solms., Alternanthera philoxeroides (Mart.) Griseb., and Pistia stratiotes L. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…For Typha domingensis, the literature review observed metals are absorbed in the roots and leaves of [21,50]. These studies revealed for nutrients though an increase in the root cross-sectional areas of Typha domingensis [21].…”
Section: Percent Of the Types Of Waste The Plants Treatedmentioning
confidence: 96%
“…For Typha domingensis, the literature review observed metals are absorbed in the roots and leaves of [21,50]. These studies revealed for nutrients though an increase in the root cross-sectional areas of Typha domingensis [21].…”
Section: Percent Of the Types Of Waste The Plants Treatedmentioning
confidence: 96%
“…These organisms are key components in natural wetlands and can serve as bioindicators of a variety of ecosystem stressors such as nutrient runoff, changes in hydrologic regime, and exotic species invasion. In addition, macrophytes may be also indicative of water contamination caused by human activities such as industrial, agricultural, and mining exploitation [1][2][3][4]. Therefore, the use of macrophytes as biomonitors of stream health should be considered as a useful tool for the management of aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…As photosynthetic organisms, they are the main primary producers fixing energy and supplying oxygen for the other ecosystem components. Macrophytes have been studied locally and around the world in relation to different aspects such as response to contaminants, phytoremediation, and biomonitoring capacity [1]- [8]. Regarding biomonitoring, Bonanno and Vymazal [9] studied the accumulation of various elements in six species of macrophytes differing in biomass size, anatomy, life cycle, and ecology.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in the Middle Parana River floodplain have demonstrated that aquatic plants have shown fast growth, high productivity, and a wide response to floods and pollutant exposition [3], [12], [13]. Besides, there are numerous local studies focused on the plant responses and the efficiency of accumulation of nutrients and metals in tissues, carried out both, in natural and constructed wetlands, and in greenhouses [8], [13]- [23].…”
Section: Introductionmentioning
confidence: 99%